Surface characterization of Langmuir-Blodgett films from bovine erythrocyte membranes (BEM) - Felsztyna, Iván (2020)
This work was aimed at designing an enzyme-based biosensor. So, Langmuir films from bovine erythrocyte membranes (LFBEM) were prepared and transferred to alkylated glasses (Langmuir-Blodgett films, LBBEM). Epifluorescence Microscopy (EFM) and Brewster Angle Microscopy (BAM) were performed on LFBEM. Additionally, EFM and Atomic Force Microscopy (AFM) were performed on LBBEM. The LBBEM was used as the enzyme source for measuring the activity of Bovine Erythrocyte Acetylcholinesterase (BEA).While the rheological behavior of LFBEM was compatible with an expanded monolayer throughout the entire isotherm, in EFM and BAM images, it exhibited a marked topographic heterogeneity which was associated to coexisting fluid domains. Remarkably, in BAM images at   30 mN/m irregular dark regions with reflectivity values similar to the clean interface were found, suggesting the presence of cracks in the film.EFM images of LBBEM roughly conserved the topography of the original LFBEM but with less heterogeneity. The AFM images of LBBEM showed some structures with < 60 nm height, which resembled closed vesicles and when transferred at 35mN/m (a bilayer equilibrium surface pressure) it exhibited a 4m wide depressed regions of 5 nm depth typical of the phase coexistence. Taken together, EFM, BAM and AFM images suggest that over the air-water interface, as well as over the silanized glass substrate, the surface is mostly covered by a monolayer with a few particles dispersed. It is worth to note that BEA present in LBBEM could retain its catalytic activity along several days of storage and maintained the expected kinetic behavior in the presence of some known enzyme modulators.In these systems, the use of natural membranes offers compositional and structural complexity allowing the study of various phenomena of biophysical and cellular interest and facilitates, the building up of biosensors based on the activity of membrane bound enzymes preserving the protein´s natural environment.